Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.2741/e687
|View full text |Cite
|
Sign up to set email alerts
|

Is vitamin D deficiency correlated with childhood wheezing and asthma

Abstract: There is increasing evidence that vitamin D regulates immune responses. There is also epidemiological evidence of a relationship between vitamin D deficiency and development of asthma. In addition, several epidemiological studies suggest that low levels of vitamin D during pregnancy and early life are inversely associated with the risk of developing respiratory infections and wheezing in childhood. Vitamin D also seems to reduce asthma exacerbation and increase the response to glucocorticoids. These findings h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 49 publications
0
6
0
1
Order By: Relevance
“…Studies have shown that vitamin D plays a role in fetal lung development and maturation as well as maintaining lung structure and function (reviewed in 25 ). In a rat model aimed at determining the effects of perinatal vitamin D deficiency on pulmonary function, females were put on a special diet (no cholecalciferol or a 250, 500 or 1,000 IU/kg cholecalciferol) one month before pregnancy, which was continued throughout pregnancy and lactation.…”
Section: Results From Animal Studiesmentioning
confidence: 99%
“…Studies have shown that vitamin D plays a role in fetal lung development and maturation as well as maintaining lung structure and function (reviewed in 25 ). In a rat model aimed at determining the effects of perinatal vitamin D deficiency on pulmonary function, females were put on a special diet (no cholecalciferol or a 250, 500 or 1,000 IU/kg cholecalciferol) one month before pregnancy, which was continued throughout pregnancy and lactation.…”
Section: Results From Animal Studiesmentioning
confidence: 99%
“…In some studies lower levels of vitamin D has been found in asthmatic patients that leads to decline in airway functions [27,28]. Vitamin D supplementation in asthmatic patients can reduce the severity of the disease and can enhance airway responsiveness to glucocorticoids [29]. However, some other studies did not find an association between vitamin D and the airways function [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…table 1). Several potential mechanisms for the programming of allergy by maternal vitamin D status were described in a recent review [105], relating it to both the innate and adaptive immune system (further described in online suppl. table 1).…”
Section: Pregnancy Diet and Nutritional Interventionsmentioning
confidence: 99%